Cognitive and Linguistic Skills Associated With Cross-Linguistic Transfer in the Production of Oral Narratives in English as a Foreign Language by Arabic- and Hebrew-Speaking Children: Finding Common Denominators - Russak, Susie; Zaretsky, Elena (Frontiers in Psychology, 2021)
Many studies have examined literacy and related skills among learners of English as a foreign language (EFL), but little attention has been given to the role of oral language within a cross-linguistic framework despite the fact that English is the most widely spoken additional language today. Oral narratives rely on lexical, morphosyntactic, and conceptual knowledge. An in-depth examination of this modality can shed light on specific associations between cognitive and linguistic L1 and EFL skills and suggest possible mediating variables that assist multilingual speakers in producing complete oral narratives in EFL. The present study examined L1 and EFL contributors to EFL oral narratives produced by native Arabic (n=85) and Hebrew (n=86) speaking 6th graders seeking to identify cross-linguistic influences. We assessed general cognitive skills, phonological memory, lexical, morphosyntactic knowledge and reading comprehension in L1 (Hebrew speakers), Modern Standard Arabic (MSA, L2), L3 Hebrew (for Arabic speakers) and EFL. The “Cookie Theft” task assessed EFL elicited narratives using modified narrative analysis scales to account for microstructure (lexical and morphosyntactic complexity) and macrostructure (understanding story elements), generating a Total Narrative score. Our results yielded different patterns of underlying psycholinguistic profiles, and cross and within language associations for each group. Strong interactions between L1, L2/L3 and EFL morphological awareness and reading comprehension suggested cross-linguistic transfer. Regression analysis identified the most influential skills supporting EFL narratives for each linguistic group: English reading comprehension was essential for Hebrew speakers and English morphological awareness for Arabic ones. These results suggested different allocations of cognitive and linguistic resources in EFL narratives. The results also allowed to identify a common mediating skill for both groups. Findings are discussed within the theoretical framework of the Interdependence Hypothesis, the Linguistic Proximity Model, as well as accounts of direct and indirect transfer, which illuminate the impact of typological distance, general language proficiency and components of linguistic knowledge on cross-linguistic transfer in EFL oral language production.